Graphene/Polyimide Nanofibrous Mat for High-Efficiency Filtration. Issue 4 (July 2022) - Meng, Depeng; Zhang, Yihe; Wu, Juntao
The development of novel nanofibrous filters has received much attention. Nanofibrous nonwoven mats are applicable in air filtration, but their structural characteristics lead to weak mechanical properties. By incorporating graphene with polyimide, we fabricated nanofibrous mats for air filtration. The results indicate that these mats are highly efficient (up to 99.1%) for air filtration and have strength improvement and thermal stability. These mats are expected to be applied for extreme conditions.